If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5x + -6(-4 + -12) = -189 Combine like terms: -4 + -12 = -16 5x + -6(-16) = -189 Multiply -6 * -16 5x + 96 = -189 Reorder the terms: 96 + 5x = -189 Solving 96 + 5x = -189 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-96' to each side of the equation. 96 + -96 + 5x = -189 + -96 Combine like terms: 96 + -96 = 0 0 + 5x = -189 + -96 5x = -189 + -96 Combine like terms: -189 + -96 = -285 5x = -285 Divide each side by '5'. x = -57 Simplifying x = -57
| x/5=31 | | v-(-6)=-3 | | 5a+2=6x-1 | | -(4y-3u-3)= | | 2f+3=11f+-24 | | 3p=-4 | | -2x-4-6y+15=-11 | | -2x-4-6y+15=11 | | -b/2(a) | | 9c=4 | | 6x/3x | | -2+7x=45 | | 4d+(-11)=2d+7 | | 2x-11+4x-22=180 | | X+51=-62 | | 15=4x-55 | | 2m+9=7m-36 | | 9x^2+4x-3=7x^2-2 | | C=5/2k-47 | | y=0.036x^2-2.8x+62.57 | | 4(4w+3)*3=-11 | | C=5/2k-37 | | (-7x+13)(-x-8)=0 | | 5(2x+3)-6(-2x+1)=9(x-2) | | 2[x-2(x-1)]-3(3y-5)=-11 | | (2x-5)2-(x+1)2=7x | | -5(2t+2)=20 | | n+(-12)=3n | | X-2x+3=4x+2 | | 9x-9=9-8x | | 8x-16-2x=34 | | 12ab-28bc+20ac=0 |